Pengaruh Strategi Marketing Mix 7P terhadap Tingkat Penjualan di Mini Kopi Green Ville - Mego, Katarina Jessie; Facrureza, Dewanta (MES Management Journal, 2024)
Business people today face great pressure to increase creativity in product marketing strategies to remain competitive in a dynamic market. The company's main goal is to achieve maximum profits, so understanding and implementing marketing strategies is very important. One business that is currently trending is a café. In Jakarta, many entrepreneurs are developing culinary businesses, especially cafes. However, with so many cafes, entrepreneurs face various conflicts such as declining sales and lack of visitor interest. Quantitative research is the method of choice. Utilizing a purposive testing technique and a non-likelihood examining methodology, 100 respondents were chosen for the example. This study utilizes numerous straight relapse examination. The consequences of the t test show that the factors item (X1), advancement (X3), and actual proof (X7) meaningfully affect the degree of deals (Y). This is known. However, deals level (Y) is significantly influenced by the factors value (X2), location (X4), individuals (X5), and process (X6). The consequences of the F test showed that the promoting blend factors (7P) at the same time affected where to go. As needs be, the goal of this study is to conclude the 7P publicizing mix strategy (X1) for More modest than ordinary Kopi, Green Ville's arrangements level (Y). This study's methodology is based on quantitative research techniques. The study's primary objective is to learn more about how Green Ville's Mini Kopi marketing strategy affects sales. The use of contextual analysis strategies is the essential focal point of this quantitative review. Meeting, noticing, and recording are a portion of the techniques utilized in this review to gather information.